Electrophoretic deposition of MnCo2O4 coating on solid oxide cell interconnects manufactured through powder metallurgy. (March 2023) - Zanchi, Elisa; Sabato, Antonio Gianfranco; Monterde, Mari Carmen; Bernadet, Lucile; Torrell, Marc; Calero, José Antonio; Tarancón, Albert; Smeacetto, Federico
Graphical abstract: Highlights: Electrophoretic deposition was successfully employed to coat complex interconnects. Area specific resistance degradation rate of 1.2 mΩ cm 2 /kh for the best coated system. A first comprehensive assessment of the synergy between powder metallurgy and electrophoretic deposition. Abstract: Developing cost-effective and durable interconnects for solid oxide cells is crucial to overcome currently existing barriers for the commercialization of this promising energy technology. A systematic microstructural and electrical characterization of MnCo2 O4 spinel coatings processed by electrophoretic deposition on SUS 445 ferritic stainless steel, manufactured through powder metallurgy, is here reviewed and discussed for application in high temperature solid oxide cells stacks. The work presents a successful combination of the powder metallurgy processing of metallic interconnects with the electrophoretic deposition as a fast and versatile approach to coat complex interconnect shapes. Therefore, this study assesses the effect of the sintering route of coated steel on the final microstructure. Remarkable results in terms of electrical properties are here presented for EPD coated sample reduced at 1000 °C and re-oxidised at 800 °C in static air, obtaining an area specific resistance degradation rate of 1.2 mΩ cm 2 /kh together with an effective limitation of Cr outward diffusion despite the prolonged exposure in relevant conditions. This novel approach opens the door for a new class of complex-shaped interconnects with enhanced performance and durability and excellent scalability at a low cost.